Kinetic analysis of decreased sperm fertilizing ability by fluorides and fluoroaluminates: a tool for analyzing the effect of environmental substances on biological events - Bosakova, Zuzana; Tockstein, Antonin; Adamusova, Hana; Coufal, Pavel; Sebkova, Natasa; Dvorakova-Hortova, Katerina (European biophysics journal, 2016)
Fluorides and fluoroaluminates decrease mouse sperm fertilizing potential by modifying the process of sperm preparation for fertilization, so-called capacitation, followed by acrosome reaction (AR). Capacitation was monitored by protein tyrosine phosphorylation (pTyr), and AR was induced consequently. The aim of this study was to apply kinetic analysis to the previously obtained dependences of pTyr and AR at capacitation times, and propose a mathematical theory for a mechanism when sperm maturation ability is amended by external stimuli. The experimental input data, previously obtained, are consistent with the proposed theory and the results of kinetic analysis show that sperm capacitation runs as two subsequent first-order steps. Firstly, an unstable intermediate is formed and then gradually decomposes. The time corresponding to the maximal production of the unstable intermediate is probably most suitable for sperm obtaining the ability to fertilize the egg. The presented calculations indicate that the application of kinetic analysis can serve as a tool to predict or confirm a course of biological events that are modified by external factors, and therefore the proposed theory shall be of interest to a broad scientific audience.
Keywords: akrozomální reakce; Mice, Inbred BALB C; Acrosome reaction; fluor; Sperm Maturation; Capacitation; mužské pohlaví; Acrosome Reaction; hliník; Mice; Aluminum; Fluoride complexes; Tyrosine phosphorylation; Sperm fertilizing ability; zvířata; zrání spermie; Fluorides; myši inbrední BALB C; Fluorine; Kinetics; myši; Spermatozoa; fluoridy; spermie; Male; Animals